2004
DOI: 10.2174/1568011043482070
|View full text |Cite
|
Sign up to set email alerts
|

Extending Natures Leads: The Anticancer Agent Ellipticine

Abstract: The natural plant product ellipticine was isolated in 1959 from the Australian evergreen tree of the Apocynaceae family. This compound was found to be an extremely promising anticancer drug. The planar polycyclic structure was found to interact with DNA through intercalation, exhibiting a high DNA binding affinity (10(6) M(-1)). The presence of protonatable ring nitrogens distinguished ellipticine from other simple intercalators. Both monocationic and uncharged species were found to be present under physiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
115
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(115 citation statements)
references
References 0 publications
0
115
0
Order By: Relevance
“…This work is, to our knowledge, the first study showing that cytochrome b 5 can alter not only the amounts but also the types of metabolites produced from a single substrate by one CYP.…”
Section: Page 7 Of 45mentioning
confidence: 89%
See 2 more Smart Citations
“…This work is, to our knowledge, the first study showing that cytochrome b 5 can alter not only the amounts but also the types of metabolites produced from a single substrate by one CYP.…”
Section: Page 7 Of 45mentioning
confidence: 89%
“…It was suggested that the major mechanisms of its antitumor, mutagenic and cytotoxic activities are (i) intercalation into DNA [4,5], and (ii) inhibition of DNA topoisomerase II activity [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mode of antitumor, cytotoxic and mutagenic action of ellipticine is considered to be based mainly on DNA damage such as intercalation into DNA [4,44], inhibition of topoisomerase II [4,[14][15][16], and formation of covalent DNA adducts mediated by CYPs and peroxidases [3,19,21,24,45]. Intercalation of ellipticine into DNA and inhibition of topoisomerase II occur in all cell types irrespective of their metabolic capacity, because of the general chemical properties of this drug and its affinity to DNA and topoisomerase II protein [4,9,45]. However, the formation of ellipticine-DNA adducts, which is dependent on ellipticine activation by CYPs and peroxidases, has not yet been proven as a general mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Ellipticine has been reported to arrest cell cycle progression by regulating the expression of cyclinB1 and Cdc2 as well as phosphorylation of Cdc2 [5,6], to induce apoptotic cell death by the generation of cytotoxic free radicals, the activation of Fas/Fas ligand system, the regulation of Bcl-2 family proteins [5][6][7][8], an increase of wild-type p53, the rescue of mutant p53 activity and the initiation of the mitochondrial apoptosis pathway [5,6,8,9]. Ellipticine also uncouples mitochondrial oxidative phosphorylation [10] and thereby disrupts the energy A c c e p t e d M a n u s c r i p t 5 balance of cells.…”
Section: ) An Alkaloid Isolated Frommentioning
confidence: 99%